2006
DOI: 10.1111/j.1523-1739.2006.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Barriers to Implementation of an Adaptive Land Management Program

Abstract: The Florida Fish and Wildlife Conservation Commission manages over 650,000 ha, including 26 wildlife management and environmental areas. To improve management, they developed an objective-based vegetation management (OBVM) process that focuses on desired conditions of plant communities through an adaptive management framework. Our goals were to understand potential barriers to implementing OBVM and to recommend strategies to overcome barriers. A literature review identified 47 potential barriers in six categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
2
26
0
2
Order By: Relevance
“…Although legal and regulatory requirements were not listed explicitly, related issues regarding management flexibility and availability of agency resources were included among the categories on logistical and institutional barriers. Their survey revealed that logistical issues were the most problematic of all barriers, specifically citing lack of agency resources and the time-consuming nature of AM protocols (Jacobson et al 2006). Similarly, Butler and Koontz (2005) surveyed 345 U.S. Forest Service managers regarding their experiences implementing the agency's ecosystem management objectives, of which AM is one component (Grumbine 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although legal and regulatory requirements were not listed explicitly, related issues regarding management flexibility and availability of agency resources were included among the categories on logistical and institutional barriers. Their survey revealed that logistical issues were the most problematic of all barriers, specifically citing lack of agency resources and the time-consuming nature of AM protocols (Jacobson et al 2006). Similarly, Butler and Koontz (2005) surveyed 345 U.S. Forest Service managers regarding their experiences implementing the agency's ecosystem management objectives, of which AM is one component (Grumbine 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The subset of this literature that specifically addresses AM implementation in the United States emphasizes the need for a more explicit commitment to AM methodologies (Moir and Block 2001, Stankey et al 2003, Benson 2010a. Jacobson et al (2006) looked at barriers to AM implementation by surveying the 90 staff members of the Florida Fish and Wildlife Conservation Commission using a questionnaire that identified 47 potential barriers to the use of AM. Although legal and regulatory requirements were not listed explicitly, related issues regarding management flexibility and availability of agency resources were included among the categories on logistical and institutional barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of resources is one of the most recognised barriers (Walters 1997;Jacobson et al 2006), particularly as adaptive management can create additional management costs. Legislation and government policies may restrict adaptive management methods (Walters 1997;Jacobson et al 2006).…”
Section: Adaptive Managementmentioning
confidence: 99%
“…Lack of resources is one of the most recognised barriers (Walters 1997;Jacobson et al 2006), particularly as adaptive management can create additional management costs. Legislation and government policies may restrict adaptive management methods (Walters 1997;Jacobson et al 2006). Protected areas are managed and operate within government policies and legislation which may or may not be flexible enough for adaptive management strategies (Young & Lipton 2006;Scheepers et al 2011).…”
Section: Adaptive Managementmentioning
confidence: 99%
See 1 more Smart Citation